HUBUNGAN LAMA MENDERITA DIABETES MELITUS DAN KADAR GULA DARAH DENGAN KADAR KOLESTEROL TOTAL PADA PASIEN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT PERTAMINA BINTANG AMIN HUSADA BANDAR LAMPUNG TAHUN 2021 - Rina Kriswiastiny; Nabila Aurelia Hidayat; Festy Ladyani Mustofa; Dessy Hermawan (Medula, 2022)
Diabetes mellitus is a metabolic disease caused by the pancreas gland being unable to produce glucose-regulating hormone (insulin) and causing hyperglycemia. PERKENI attaches that Indonesia has experienced an increase in ranking from 7th to 5th with the highest number of diabetics in the world. If diabetes mellitus is not treated seriously, there will be microvascular complications that trigger coronary heart disease due to the buildup of cholesterol in the blood vessels. This study aims to determine whether there is a long-standing relationship with type 2 diabetes mellitus and blood sugar levels with total cholesterol levels in the outpatient polyclinic of Pertamina Bintang Amin Husada Hospital Bandar Lampung in 2021. The type of this study was observational analytic with cross sectional method using purposive sampling. as many as 83 samples of type 2 DM patients who met the inclusion criteria. Based on the results of the study with a total of 83 samples, the majority of the sexes were female 48 people (57.8%), age >45 years were 59 people (71.1%), duration of suffering >1 year were 57 (68.7%), levels of blood sugar when (GDS) <200 mg/dl as many as 42 people (50.6%). And cholesterol levels > 200 mg/dl as many as 62 people (74.7%). The results of the Spearman correlation between the length of suffering from type 2 diabetes and total cholesterol obtained p = 0.037 and r = + 0.229. In the results of the Spearman correlation, the relationship between blood sugar levels and total cholesterol obtained a value of p = 0.000 and r = + 0.394, because the value of p = 0.000 and p = 0.037 <0.05 so that it can be stated that there is a significant relationship between variables